dewi PENERAPAN MEDIA BIGBOOK UNTUK MENINGKATKAN KEMAMPUAN BAHASA RESEPTIF PADA ANAK USIA 4-5 TAHUN DI RAUDHATUL ATHFAL MIFTAHUL ULUM JATISARI - Dewi Hermawati Ningsih; Indriana Warih Windasari (incrementapedia, 2022)
From the results of initial observations it is known that the receptive language skills of Group A children in Raudhatul Atfhal Miftahul Ulum Jatisari are still not developed. This is because the ability to read is still lacking. Lack of language in children causes children to be less active in telling stories, in terms of answering a question correctly when asked, and also not being able to retell a story that has been heard. Therefore, research was carried out by applying the media of picture story books to increase children's enthusiasm for reading and storytelling skills in children. In this study, the Classroom Action Research (CAR) method was used with a total of 15 students in group A, of which 6 male students and 9 female students. By using picture story media (bigbook) in improving the ability to tell stories in children. The results of the study state that bigbook media is very effective in learning in early childhood, and can improve children's storytelling skills.